2015
DOI: 10.1175/jas-d-14-0025.1
|View full text |Cite
|
Sign up to set email alerts
|

In situ Measurements of Momentum Fluxes in Typhoons

Abstract: One of the scientific objectives of the U.S. Office of Naval Research–sponsored Impact of Typhoons on the Ocean in the Pacific (ITOP) campaign was improved understanding of air–sea fluxes at high wind speeds. Here the authors present the first-ever direct measurements of momentum fluxes recorded in typhoons near the surface. Data were collected from a moored buoy over 3 months during the 2010 Pacific typhoon season. During this period, three typhoons and a tropical storm were encountered. Maximum 30-min sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…French et al (2007) found a roll-off at a much lower wind speed of about 21 ms −1 using direct observations from an aircraft, although they claimed to remain uncertain. A similar result obtained by Potter et al (2015) showed evidence of a rolloff C D at a wind speed of 22 ms −1 with the direct buoy observations in typhoons. Based on the wind profile measured from a tower, Zhao et al (2015) revealed that C D begins to decrease at wind speeds of 24 ms −1 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…French et al (2007) found a roll-off at a much lower wind speed of about 21 ms −1 using direct observations from an aircraft, although they claimed to remain uncertain. A similar result obtained by Potter et al (2015) showed evidence of a rolloff C D at a wind speed of 22 ms −1 with the direct buoy observations in typhoons. Based on the wind profile measured from a tower, Zhao et al (2015) revealed that C D begins to decrease at wind speeds of 24 ms −1 .…”
Section: Discussionsupporting
confidence: 85%
“…Based on the wind profile measured from a tower, Zhao et al (2015) revealed that C D begins to decrease at wind speeds of 24 ms −1 . However, with the high-resolution wind profiles collected with GPS drop sondes, reported that C D begins to decrease at a wind speed of about 40 ms −1 , which is much greater than those of French et al (2007), Potter et al (2015) and Zhao et al (2015). It is clear that the critical wind speeds for maximum C D need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…The coupling resulted in more uniform peak and HF wave directions which no longer pointed in the wind direction. The high frequency waves were pulled away from the wind direction, ostensibly through interaction with the peak waves, and steered a shift in wind stress away from the wind direction as observed in Potter et al ().…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of discarded samples deviated from −5/3 power law, which indicated that the similarity theory was not satisfied [ Kaimal et al ., ]. If the temporal variation of the cumulative summation affects the total momentum flux sharply, the samples were also rejected [ French et al ., ; Potter et al ., ]. Only if the ogive curve approaches asymptotically a single value, the corresponding data can meet the stationary condition for the measurement and would be accepted [ French et al ., ; Potter et al ., ].…”
Section: Methodsmentioning
confidence: 99%